Optimal prime mover size determination of a CCHP system based on 4E analysis. (November 2021) - Xu, Jian; Yao, Yanfei; Yousefi, Naser
Abstract: The optimum size of the prime mover (PM) for combined cooling, heating and power (CCHP) systems is determined taking account of economics, environmental impacts, energy, and exergy. The optimum size of the PM greatly increases the justification of establishing a CCHP system. Optimum sizing of the PM is conducted here considering exergy efficiency, exergy destruction rate, total energy efficiency, overall fuel energy consumption, carbon release, carbon release decrease, equivalent uniform annual benefit, and payback duration. To determine the optimum size, an objective function is presented in which some of the aforementioned criteria are minimized and some others are maximized. To solve the problem arisen from this objective function, the improved pathfinder optimization algorithm is proposed. To prove its superior performance, it is compared to six other popular optimization algorithms used in CCHP optimization using six benchmark functions. After obtaining the optimum size of the PM, sensitivity analyses are conducted on all of the eight assessment sub-criteria versus the PM capacity, and the results are given in figures. In addition, their values are given with the optimum size of the PM. The results indicate that the studied CCHP with the optimum PM size yields exergy efficiency of 55.53%, exergy destruction rate of 48.34%, total energy efficiency of 68.79%, and overall fuel energy consumption of 209 kWh. Also, this system will produce 36.82kg of carbon per hour which is 23.46% lower than the initial separated generation system. Moreover, with the equivalent uniform annual benefit of 26376, it will pay back in 3.21 years.